OFR-98-77 Rapid Excavation Of Rock With Small Charges Of High Explosives - George B. Clark (The National Institute for Occupational Safety and Health (NIOSH), 1976)
The purpose of this investigation was to determine the feasibility of designing and testing the elements of a small charge blasting system which will eliminate, or reduce to acceptable levels, most of the undesirable features of current underground drill and blast systems, i.e., 1) air blast, 2) ground vibrations, 3) flying fragments, 4) overbreak and fracture of surrounding rock, and 5) the cyclic nature of drill and blast operations. The experimentation was conducted in tunnels in granite and the results indicate that the basic technical concepts of the project were achieved. The next step is to design, construct, and test a prototype machine.